Tropical Temperate Toughs over southern Africa: mechanisms and evolution in response to climate change - (:unkn) unknown (My University, 2015)
In the Southern Hemisphere, Southern Africa and the south-west Indian Ocean are one of the three preferred regions where interactions between the tropics and midlatitudes develop. This is the South Indian Convergence Zone (SICZ), where northwest-southeast oriented cloud bands form at the synoptic scale (between 3 and 5 days). These bands are mainly found during the austral summer and are commonly referred to as tropical temperate troughs (TTTs). This research aims at improving our knowledge related to TTTs, with a study on the dynamics associated with these systems, and an analysis of their possible evolution during the 21st century.The first part of this thesis aims at identifying favorable conditions for the formation and the development of TTTs. Weather regimes analysis is used to identify TTTs on the one hand and mid-latitude perturbations on the other hand, allowing us to better document the spatial and temporal variability of TTTs together with background climate conditions. The events identified account for 20% of seasonal rainfall on average. Their contribution increases according to a west to east gradient. The comparison between these two classifications, partitioned using a k-means clustering, first confirms that midlatitude perturbations are a necessary condition for TTT development, but they are not sufficient. An excess of moist static energy over the Mozambique Channel partly supplied by advections from remote regions (mostly the southern Atlantic basin and the south-west Indian Ocean) form additional conditions favoring deep atmospheric convection over and near the Southern Africa.The second part investigates possible changes in precipitation, TTTs and more generally climate over Southern Africa during the 21st century in response to radiative forcing associated with greenhouse gas emissions (GHG). A multi-model (height climate models taken on the IPCC Fifth Assessment Report) and multi-scenario (RCP 8.5 and 2.6) approach is chose
Keywords: African Research